In vitro expansion of mouse primordial germ cell‐like cells recapitulates an epigenetic blank slate. (30th May 2017) - Ohta, Hiroshi; Kurimoto, Kazuki; Okamoto, Ikuhiro; Nakamura, Tomonori; Yabuta, Yukihiro; Miyauchi, Hidetaka; Yamamoto, Takuya; Okuno, Yukiko; Hagiwara, Masatoshi; Shirane, Kenjiro; Sasaki, Hiroyuki; Saitou, Mitinori
Abstract: The expansion of primordial germ cells (PGCs), the precursors for the oocytes and spermatozoa, is a key challenge in reproductive biology/medicine. Using a chemical screening exploiting PGC‐like cells (PGCLCs) induced from mouse embryonic stem cells (ESCs), we here identify key signaling pathways critical for PGCLC proliferation. We show that the combinatorial application of Forskolin and Rolipram, which stimulate cAMP signaling via different mechanisms, expands PGCLCs up to ~50‐fold in culture. The expanded PGCLCs maintain robust capacity for spermatogenesis, rescuing the fertility of infertile mice. Strikingly, during expansion, PGCLCs comprehensively erase their DNA methylome, including parental imprints, in a manner that precisely recapitulates genome‐wide DNA demethylation in gonadal germ cells, while essentially maintaining their identity as sexually uncommitted PGCs, apparently through appropriate histone modifications. By establishing a paradigm for PGCLC expansion, our system reconstitutes the epigenetic "blank slate" of the germ line, an immediate precursory state for sexually dimorphic differentiation. Synopsis: Stimulation of cAMP signaling provides a means to in vitro culturing competent primordial germ cell‐like cells (PGCLCs), which has remained a major challenge in reproductive biology, and allows the characterization of their epigenetic and transcriptional states, mirroring those occurring during gonadal germ cell development. cAMP signaling stimulation by forskolin and rolipram increases in vitro proliferation of mouse embryonic stem cell‐derived PGCLCs up to ˜50 fold. Expanded PGCLCs continue to proliferate in culture beyond day 6 and contribute robustly to spermatogenesis and fertile offspring in vivo after transplantation. Expanded PGCLCs maintain their transcriptome and histone modification states, analogous to a sexually uncommitted PGC state. Expanded PGCLCs comprehensively erase their DNA methylome. Abstract : cAMP signaling agonists stimulate in vitro proliferation of murine primordial germ cell like cells, accompanied by loss of DNA methylation patterns.